ESG and Financial Performance: The Moderating Role of Intellectual Capital - Puti Azzahra Vania Eriany; Luluk Widyawati (EQUITY, 2024)
Public awareness of social and environmental challenges has raised attention to ESG issues around the world.  This study aims to empirically examine the effect of ESG on corporate financial performance with the moderating role of intellectual capital and its components human capital, structural capital, and relational capital. ESG measurement is measured by ESG score, financial performance is measured by ROA and Tobins'Q, and intellectual capital is measured by VAIC. The research was conducted on 424 samples of companies in ASEAN-5 countries (Indonesia, Malaysia, Singapore, Thailand, Philippines) obtained through puposive sampling technique with the research period 2019-2022. The results prove that ESG is positively related to financial performance on the proxy of ROA. Intellectual capital strengthens the relationship between ESG and corporate financial performance on ROA and Tobins'Q proxies. Structural capital strengthens the relationship between ESG and financial performance on the Tobins'Q proxy. Relational capital strengthens the relationship between ESG and corporate financial performance on the ROA proxy. Meanwhile, human capital weakens the relationship between ESG and corporate financial performance.   Keywords: ESG, Financial Performance, ROA, Tobins’Q, Intellectual Capital, Human Capital, Structural Capital, Relational Capital